Analysis of Oxygen Transport in Cathode Catalyst Layer of Low‐Pt‐Loaded Fuel Cells. Issue 3 (15th December 2014) - Choo, Min‐Ju; Oh, Keun‐Hwan; Park, Jung‐Ki; Kim, Hee‐Tak
Abstract Oxygen transport resistance, one of the causes of large polarization in the cathode catalyst layer (CL), is intensified in low‐Pt‐loaded polymer electrolyte membrane fuel cells (PEMFCs). In order to explore operation strategies and cathode design to mitigate the large oxygen transport resistance of low‐Pt‐loaded fuel cells, the influence of operating conditions and ionomer structure on oxygen transport in the CL is investigated. Remarkably, the oxygen transport resistance data for different operation conditions and ionomer structures lie on a single curve when they are plotted as a function of the water partial pressure of the feed. At a high water partial pressure of 80 kPa, the oxygen transport resistance of the low‐Pt‐loaded CL (0.14±0.03 mg−Pt cm−2) becomes comparable to that of the high‐Pt‐loaded CL (0.40±0.04 mg−Pt cm−2) as a result of the opposing influences of Pt loading on Knudsen and ionomer film diffusion. This emphasizes the importance of the water uptake in the ionomer film for reducing oxygen transport in the CL. From a fuel cell design perspective, the operation strategy and CL design to maintain high water partial pressure in the cathode CL are extremely important for realizing low‐Pt‐loaded fuel cells.